The determinants of earnings inequalities: Panel data evidence from South Africa - Andrew Kerr; Francis J. Teal (Institute for the Study of Labor (IZA), 2012)
In this paper we analyse the relative importance of individual ability and labour market institutions, including public sector wage setting and trade unions, in determining earnings differences across different types of employment. To do this we use the KwaZulu-Natal Income Dynamics Study data from South Africa, which show extremely large average earnings differentials across different types of employment. Our results suggest that human capital and individual ability explain much of the earnings differentials within the private sector, including the union premium, but cannot explain the large premiums for public sector workers. We show that a public sector premium exists only for those moving into the public sector. The paper addresses the challenges of non-random attrition and measurement error bias that panel data bring. Our results show that emphasising a simple binary dichotomy between the formal and informal sector can be unhelpful in attempting to explore how the labour market functions.
urn:nbn:de:101:1-201208174784
Keywords: J31; J51; J45; O12; 330; formality; trade unions; public sector; earnings; South Africa; Einkommen; Lohnstruktur; Informeller Sektor; Öffentlicher Dienst; Südafrika